Perdagangan Satwa Dilindungi Sebagai Bentuk Kejahatan Lingkungan - Asti Anindya Khoerunisa; Afwany Hisaaby; Anaku Alana; Sarah Tyas Prameswari; Yuyun Meliyani (Adagium: Jurnal Ilmiah Hukum, 2026)
This study aims to analyze the reasons why the trade in protected wildlife can be classified as an environmental crime, the forms of legal liability imposed on offenders within the Indonesian environmental law system, and the role of environmental law enforcement in preventing the extinction of protected species. This research employs a normative juridical method with a descriptive qualitative approach. Data were obtained through library research by examining statutory regulations, legal literature, textbooks, and relevant scholarly journal articles related to the conservation of biological natural resources and environmental crimes. The findings indicate that the trade in protected wildlife constitutes not merely an ordinary criminal offense, but an environmental crime that causes serious ecological impacts, including ecosystem degradation, loss of biodiversity, and threats to species extinction. Legal liability for offenders may be imposed through administrative, criminal, and civil sanctions cumulatively. The study also finds that the effectiveness of environmental law enforcement plays a crucial role in protecting wildlife, although in practice it still faces various challenges, such as weak deterrent effects and low public legal awareness. This study is expected to strengthen the environmental law perspective in addressing protected wildlife trade and to serve as a reference for the development of more comprehensive and sustainable policies and law enforcement strategies.